Effects of season, temperature, and body mass on the standard metabolic rate of tegu lizards (Tupinambis merianae) - Toledo, Luis F. [UNESP]; Brito, Simone P. [UNESP]; Milsom, William K.; Abe, Augusto Shinya [UNESP]; Andrade, Denis V. [UNESP] (Univ Chicago Press, 2008)
This study examined how the standard metabolic rate of tegu lizards, a species that undergoes large ontogenetic changes in body weight with associated changes in life-history traits, is affected by changes in body mass, body temperature, season, and life-history traits. We measured rates of oxygen consumption ((V) over dot o(2)) in 90 individuals ranging in body mass from 10.4. g to 3.75 kg at three experimental temperatures ( 17 degrees, 25 degrees, and 30 degrees C) over the four seasons. We found that standard metabolic rate scaled to the power of 0.84 of body mass at all experimental temperatures in all seasons and that thermal sensitivity of metabolism was relatively low (Q(10) approximate to 2.0-2.5) over the range from 17 degrees to 30 degrees C regardless of body size or season. Metabolic rates did vary seasonally, being higher in spring and summer than in autumn and winter at the same temperatures, and this was true regardless of animal size. Finally, in this study, the changes in life-history traits that occurred ontogenetically were not accompanied by significant changes in metabolic rate.